2020
DOI: 10.1016/j.jallcom.2020.155007
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of nanostructured immiscible Cu–Ta alloys processed by high-pressure torsion

Abstract: Nanostructured Cu-Ta alloys show great potential as high strength nanocrystalline materials due to their excellent mechanical properties and limited grain growth at high temperatures. This report describes the fabrication of nanostructured immiscible Cu-Ta alloys in bulk by high-pressure torsion (HPT) using a stack of Cu/Ta/Cu discs at room temperature.A microstructural study after HPT processing showed that the internal Ta layer breaks into small individual flakes which distribute uniformly over the Cu matrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…[37] Mousavi et al measured average Vickers microhardness of the annealed Ta (%200 HV). [38] Furthermore, Singh et al claimed that the microhardness of pure Nb was lower than that of pure Ta, which is in agreement with the result obtained in our study. [39] The diffusion layers with Nb and Ta interlayers give the hardness of 519 AE 99 HV 0.1 and 533 AE 46 HV 0.1 , respectively, both higher than that without interlayer.…”
Section: Mechanical Characterizationsupporting
confidence: 93%
“…[37] Mousavi et al measured average Vickers microhardness of the annealed Ta (%200 HV). [38] Furthermore, Singh et al claimed that the microhardness of pure Nb was lower than that of pure Ta, which is in agreement with the result obtained in our study. [39] The diffusion layers with Nb and Ta interlayers give the hardness of 519 AE 99 HV 0.1 and 533 AE 46 HV 0.1 , respectively, both higher than that without interlayer.…”
Section: Mechanical Characterizationsupporting
confidence: 93%
“…where k 0 is the pre-exponential factor and Q is the effective activation energy of the sintering process. According to Equations (2) and 3under isothermal conditions (k = const), we have a linear dependence:…”
Section: Spark Plasma Sintering: Kineticsmentioning
confidence: 99%
“…Copper-based composites, which involve immiscible elements (e.g., Cr, W, Mo), so-called pseudo-alloys, have attracted a vast of attention for a variety of applications including a new generation of electrical contacts, electrodes for point welding, and radiators, etc. [1][2][3][4][5][6]. Due to a unique combination of thermal, electrical, and mechanical properties as well as being corrosion resistant under applied high-voltage, such materials have found specific use as the electrodes in vacuum interrupters of high-voltage electric circuits [7].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its unique properties, the idea of obtaining composite materials consisting of a metal matrix and graphene has been developed for the past decades. It was found that the introduction of graphene into a metal matrix results in an increase its mechanical resistance and strength [ 6 , 7 , 8 , 9 , 10 ]. Graphite inclusions improve the impact strength of layered carbon/Ni and carbon/Cu composites [ 11 ].…”
Section: Introductionmentioning
confidence: 99%